Piperonylonitrile solubility in thirteen pure solvents: Determination, Correlation, Hansen solubility parameter, solvent effect and thermodynamic analysis. (November 2020) - He, Haixia; Wan, Yameng; Sun, Renren; Zhang, Pengshuai; Jiang, Gaoliang; Sha, Jiao; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of piperonylonitrile in thirteen pure solvents was measured. Hansen solubility parameter was employed to explain solubility behaviors. Solvent effect was studied in terms of solvent–solvent and solute–solvent interactions. Solubility was correlated by five thermodynamic models. Mixing thermodynamic properties were calculated by UNIQUAC model. Abstract: This work was to investigate piperonylonitrile in terms of its solid–liquid equilibrium solubility in thirteen pure solvents by employing laser monitoring technique. Solubility measurements were completed in range of temperature at (288.15–323.15) K in 1, 4-dioxane and at (278.15–323.15) K in isopropanol, 2-methoxyethanol, ethanol, ethyl acetate, methanol, n -propanol, n -propyl acetate, N, N-dimethylformamide (DMF), isopropyl acetate, methyl acetate, acetone as well as acetonitrile under 0.1 MPa. The holistic solubility profile showed that piperonylonitrile solubility in all measured solvents was proportional to the increasing of test temperature. It was also found that the mole-fraction solubility values of piperonylonitrile in measured solvents at 298.15 K exhibited a sequence of: DMF (0.2636) > 1, 4-dioxane (0.2212) > methyl acetate (0.1838) > acetone (0.1813) > ethyl acetate (0.1657) >  n -propyl acetate (0.1486) > acetonitrile (0.1435) > isopropyl acetate (0.1295) > 2-methoxyethanol (0.1010) > methanol (0.01915) > ethanol (0.01664) >  n -propanol (0.01594) > isopropanol (0.01268). The miscibility and solubility order of piperonylonitrile were further revealed by the means of Hansen solubility parameter, demonstrating that solubility behaviors could be well explained by the comprehensive action of various solubility parameters. Besides, the influence on the piperonylonitrile solubility of solute–solvent interaction and solvent–solvent interaction was illustrated via the KAT-LSER model. It was figured out that hydrogen bonding acidity and hydrogen bonding basicity exerted unfavorable influence on piperonylonitrile solubility. Moreover, the measured piperonylonitrile solubility was fitted with Wilson, NRTL, UNIQUAC, Two-Suffix Margules and NRTL-SAC model, and correlation of experimental results with the use of five activity coefficient models showed that sufficient agreement with the calculated data. Finally, the thermodynamic quantities (Δ mix H, Δ mix G and Δ mix S ) of the mixing process in different solvents were computed based on measured solubility values and UNIQUAC model. The results demonstrated that the mixing process was entropy-driven and spontaneous.